The efficacy of transcranial magnetic stimulation on migraine: a meta-analysis of randomized controlled trails - Lan, Lihuan; Zhang, Xiaoni; Li, Xiangpen; Rong, Xiaoming; Peng, Ying (Journal of headache and pain, 2017)
Objectives As a non-invasive therapy, whether transcranial magnetic stimulation (TMS) is effective on migraine. This article was aimed to assess the efficacy of TMS on migraine based on randomized controlled trails (RCTs). Methods We searched PubMed, Embase and Cochrane Library electronic databases for published studies which compared TMS group with sham group, conducted a meta-analysis of all RCTs. Results Five studies, consisting of 313 migraine patients, were identified. Single-pulse transcranial magnetic stimulation is effective for the acute treatment of migraine with aura after the first attack ( p = 0.02). And, the efficacy of TMS on chronic migraine was not significant (OR 2.93; 95% CI 0.71–12.15; p = 0.14). Conclusions TMS is effective for migraine based on the studies included in the article.